Answer:
1) s(3) = -32 feet.
2)v(5) = 3 feet/sec
3)a(4) = 12
![feet/s^(2)](https://img.qammunity.org/2020/formulas/engineering/college/l7qym60q5fhcdkkon0b3zgsc4c6ox6huzq.png)
4) Velocity becomes zero at t = 5 seconds
Step-by-step explanation:
Given that position as a function of time is
![s(t)=t^(3)-6t^(2)-15t+40](https://img.qammunity.org/2020/formulas/engineering/college/v58fgo9pqpjk0rdojwin93r8tb8qpuoxrh.png)
Now by definition of velocity we have
![v=(ds)/(dt)\\\\v=(d)/(dt)(t^(3)-6t^(2)-15t+40)\\\\\therefore v(t)=3t^(2)-12t-15](https://img.qammunity.org/2020/formulas/engineering/college/56jc3qs0kv177w9jp1z8zahr2beyklet4n.png)
Now by definition of acceleration we have
![a=(dv)/(dt)\\\\a=(d)/(dt)(3t^(2)-12t-15)\\\\\therefore a(t)=6t-12](https://img.qammunity.org/2020/formulas/engineering/college/2nzuyq7nrubj0nwhqhad1hngdlrmz0j1an.png)
Applying values of time in corresponding equations we get
1) s(3)=
![3^(3)-6* (3)^(2)-15* 3+40=-32feet](https://img.qammunity.org/2020/formulas/engineering/college/3r4uleoa07lbdrxrsrsup2svjtqa15gi6u.png)
2)v(5)=
![3* {5}^(2)-12* 5-15=3feet/sec](https://img.qammunity.org/2020/formulas/engineering/college/m4ivcmng9zcdx2gar6f64ie5yvxkhjoxlz.png)
3)a(4)=
![6* 4-12=12ft/s^(2)](https://img.qammunity.org/2020/formulas/engineering/college/11moc1ak1jwht0ihc84v4e2aqr08vbltr6.png)
4)To obatin the time at which velocity is zero equate the velocity function with zero we get
![3t^(2)-12t-15=0\\\\t^(2)-4t-5=0\\\\t^(2)-5t+t-5=0\\\\t(t-5)+1(t-5)=0\\\\(t-5)(t+1)=0\\\\\therefore t=5\\\\or\\\therefore t=-1](https://img.qammunity.org/2020/formulas/engineering/college/rvejx0gbrc7k7wjuwyhlf9rud6lwruqsaa.png)
Thus the correct time is 5 seconds at which velocity becomes zero.